2010
DOI: 10.1096/fj.09-151159
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of CUG RNA repeats causes stress and inhibition of translation in myotonic dystrophy 1 (DM1) cells

Abstract: The purpose of this study was to investigate the role of the mutant CUGn RNA in the induction of stress in type 1 myotonic dystrophy (DM1) cells and in the stress-mediated inhibition of protein translation in DM1. To achieve our goals, we performed HPLC-based purification of stress granules (SGs), immunoanalysis of SGs with stress markers TIA-1, CUGBP1, and ph-eIF2, site-specific mutagenesis, and examinations of RNA-protein and protein-protein interactions in myoblasts from control and DM1 patients. The cause-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
149
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(156 citation statements)
references
References 48 publications
5
149
2
Order By: Relevance
“…The effect of GFP transcription as a possible toxic factor was assessed previously. 38 It was shown that GFP expression did not induce significant changes in ph-eIF2 levels in the selected cells, indicating that the cells were not under stress. 38 2476 Jones et al AJP November 2011, Vol.…”
Section: Generation Of Double-stable Inducible Clonesmentioning
confidence: 95%
See 4 more Smart Citations
“…The effect of GFP transcription as a possible toxic factor was assessed previously. 38 It was shown that GFP expression did not induce significant changes in ph-eIF2 levels in the selected cells, indicating that the cells were not under stress. 38 2476 Jones et al AJP November 2011, Vol.…”
Section: Generation Of Double-stable Inducible Clonesmentioning
confidence: 95%
“…Our previous work with CUG-inducible CHO cells showed that the levels of CUG 914 RNA at 17 to 24 hours after Dox addition are similar to the levels of the mutant DMPK mRNA in human myoblasts from the patient with DM1. 38 Comparison of CUG 914 and CUG 25 expression on the same gel indicated that the efficiency of CUG 25 RNA expression was significantly higher than that of CUG 914 RNA ( Figure 1B). Although the accumulation of CUG 914 was barely visible at 7 hours after Dox addition, the signals of CUG 25 at this time point were very strong.…”
Section: Analysis Of Dox-dependent Regulation Of Transcription Of Shomentioning
confidence: 96%
See 3 more Smart Citations